A serum fucolectin isolated and characterized from sea bass Dicentrarchus labrax - Cammarata, Matteo; Vazzana, Mirella; Chinnici, Cinzia; Parrinello, Nicolò (Biochimica et biophysica acta, 2001)
A lectin specific for fucose and galactose was isolated by affinity chromatography on Sepharose CL-6B from the serum of Dicentrarchus labrax. The hemagglutinating activity against rabbit erythrocytes was calcium-independent, and reached its maximum at 37°C. Two protein components were found in the hemagglutinating fractions eluted from the Sepharose column. Only the 34 kDa component (DLL2) eluted from the polyacrylamide gels (SDS–PAGE) showed agglutinating activity against rabbit erythrocytes. SDS–PAGE, in non-reducing conditions, revealed a single 66 kDa protein that reacted with antibodies to the 34 kDa component. Therefore, a dimeric structure stabilized by disulfide bonds can be proposed. The Ca 2+-independent fucose-binding specificity, a significant amino acid sequence homology of the N-terminal trait, and cross-reaction of eel fucolectin with antibodies to DLL2 suggest that this lectin may be included in the recently identified fucolectin family.